Perancangan User Experience Aplikasi Salon Online dalam Menghadapi Pandemi di Lina Salon - Alsiendo Dewantara; Ratih Kartika Dewi; Riswan Septriayadi Sianturi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Covid-19 pandemic has brought losses to many parties. Since the pandemic, salon businesses in cities and regions have experienced large turnover losses that have brought the business to a standstill. Lina Salon is one of the salon businesses in the Pacitan area, East Java which has been running for more than 20 years. Although the business has been running for 20 years and is well known by the local community, Lina Salon's customers are increasingly quiet and have experienced a decrease in turnover of more than 50%. With the hope of reconnecting the disconnect between Lina Salon's business goals and the needs of its customers, the researcher designed an online salon application user experience so that Lina Salon's customers can still carry out beauty treatments and Lina Salon's business can resume running. The method used is design thinking because from existing research, design thinking can produce innovative solutions to problems. The final result of this research is a high-fidelity prototype with good usability value. The value of the three usability aspects obtained is for the effectiveness aspect, from the user side it produces a value of 91% and the admin side produces a value of 90%. In the aspect of efficiency using time-based efficiency, from the user side it produces a value of 0.282 goals/sec and the admin side produces a value of 0.083 goals/sec. Then to test the usability aspect of satisfaction using the SUS questionnaire, from the user side it produces a value of 80% and from the admin side, it produces a value of 83.125%.